Application of intervention mapping in cybersecurity education design - Pirta-Dreimane, Rūta; Brilingaitė, Agnė; Majore, Ginta; Knox, Benjamin James; Lapin, Kristina; Parish, Karen; Sütterlin, Stefan; Lugo, Ricardo Gregorio (Frontiers in Education, 2022)
Education in Cybersecurity is considered one of the key challenges facing the modern digitised world. Several frameworks (i.e. NIST, NICE) have defined requirements for cybersecurity education but do not give recommendations for their development. Developing appropriate education offerings need to incorporate theory-based approaches that are evidence supported. Adopting the Intervention Mapping paradigm, we propose an educational framework incorporating validated theoretical and evidence-based approaches to cybersecurity education encompassing stakeholder's input, identified competency needs, and how to implement and evaluate learning outcomes. This paper will present how Intervention Mapping can be used to help design cybersecurity education, discuss challenges in educational and professional aspects of cyber security, and present an applied educational approach based on Intervention Mapping and its evaluation.